Identifying the active compounds and mechanism of action of Banxia Xiexin decoction for treating ethanol-induced chronic gastritis using network pharmacology combined with UPLC–LTQ–Orbitrap MS. (August 2021) - Ji, Wanli; Wang, Tingting; Xu, Yanwen; An, Rui; Liang, Kun; Wang, Xinhong
Graphical abstract: Highlights: UPLC-MS/MS showed the active compounds of BXD for treating gastritis. Network pharmacology uncovered the mechanism of BXD in treating gastritis. SPR assessed the affinity between the active ingredients and potential targets. ICAM-1, PPAR-γ, and MAPK14 might become novel drug targets for gastritis. Abstract: Background: Banxia Xiexin decoction (BXD), a traditionally prescribed Chinese medicine, has been used to treat chronic gastritis for many years. However, the underlying mechanism and targets for its effects remain unknown. In the present study, we predicted the targets and active compounds of BXD in the treatment of chronic gastritis through network pharmacology and ultra-performance liquid chromatography coupled with linear trap quadrupole–Orbitrap mass spectrometry (UPLC–LTQ–Orbitrap MS). Method: A chronic gastritis model was established in rats by oral administration of 56 % ethanol. BXD was orally administered for 7 days. Stomach tissues were collected for histopathological analysis, and tumour necrosis factor (TNF)-α, interleukin (IL)-2, IL-8, and lactate dehydrogenase (LDH) levels were measured by enzyme-linked immunosorbent assay. UPLC–LTQ–Orbitrap MS was established to analyse compounds in rat plasma following oral BXD administration. The absorbed ingredients were selected as candidate active compounds. The chronic gastritis-related targets were screened using multiple databases. The potential targets for the treatment of chronic gastritis were used to construct a protein–protein interaction (PPI) network and were also analysed using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Finally, molecular docking was used to uncover the interaction between multi-components and putative targets, and the results were verified by surface plasmon resonance (SPR). Results: Intragastric administration of BXD ameliorated stomach injury resulting from chronic gastritis in rats and decreased the levels of TNF-α, IL-2, IL-8, and LDH. A comprehensive systematic strategy was used to successfully identify 38 candidate targets and 14 active compounds in BXD. Based on the network of compounds–targets and PPI, three hub genes that were associated with BXD therapy for chronic gastritis were selected and included intercellular adhesion molecule-1, peroxisome proliferator-activated receptor gamma and mitogen-activated protein kinase 14. The results of molecular docking and SPR demonstrated that the active compounds in BXD demonstrate affinity for these targets. Additionally, an enrichment analysis revealed that treatment of chronic gastritis with BXD primarily involves cytokine activation, the inflammatory response and nuclear factor-kappa B, hypoxia-inducible factor-1, phosphatidylinositol-3-kinase–protein–serine–threonine kinase and Janus kinase–signal transducer and activator of transcription signalling pathways, which may mediate the effects of BXD in the treatment of chronic gastritis. Conclusion: BXD exhibits a therapeutic effect in ethanol-induced gastritis through multi-compound, multi-target and multi-pathway mechanisms. A strategy of network pharmacology combined with SPR may provide a feasible approach to explore the targets of herbal medicine and uncover novel bioactive components.